The Effect of Compensation and Work Environment on Employee Performance - Atarnis Cahaya Lombu; Yunita Fitri Wahyuningtyas (LifeSciFi, 2026)
Human resources constitute a strategic asset that plays a vital role in the sustainability and success of an organization, with employee performance serving as a key indicator of effective HR management. This study aims to analyze the effect of compensation and work environment on employee performance, both partially and simultaneously. A quantitative research design with an associative approach was employed, involving all 55 permanent employees as respondents using a saturated sampling technique. Data were collected through structured questionnaires and direct observation and analyzed using multiple linear regression and statistical assumption tests with SPSS. The findings reveal that both compensation and work environment, individually and simultaneously, have a significant positive effect on employee performance. Adequate and fair compensation enhances employee motivation, satisfaction, and loyalty, while a supportive, safe, and comfortable work environment improves focus, efficiency, and work engagement. The practical implication is that organizations should implement competitive and equitable compensation systems and cultivate a conducive work environment to optimize employee performance and achieve strategic organizational objectives. In conclusion, effective management of internal organizational factors is essential for maximizing employee productivity, motivation, and effectiveness.